Antioxidant Capacity and Total Phenolic Compounds of Twelve Selected Potato Landrace Clones Grown in Southern Chile [Capacidad Antioxidante y Compuestos Fenólicos Totales de Una Selección de Doce Variedades Tradicionales de Papa Cultivadas en la Región Sur de Chile] - Lemus-Mondaca, R (Instituto de Investigaciones Agropecuarias, INIA, 2012)
Colored potatoes (Solanum tuberosum L.) provide a natural source of phytochemicals that help reduce the risk of diseases. However, there is a lack of information on the degree of variation of the antioxidant activity and polyphenolic contents of these native potatoes. Thus, the antioxidant activity (AA) and total phenolic content (TPC) of native Chilean potatoes were determined. Twelve potato landrace clones collected from established cultivations on Chiloe Island and Valdivia were selected. Total phenolic content and AA were compared with two commercial varieties, Shepody and Desirée. Total phenolic content was determined by the Folin-Ciocalteu method, and ?-carotene bleaching was used to compare AA. The TPC varied in the peeled potato samples from 191 to 1864 mg 100 g-1 DM meanwhile these parameters varied from 345 to 2852 mg 100 g-1 DM in unpeeled samples. Antioxidant activity was higher in unpeeled potatoes, and was the highest in the unpeeled NG-6 or Bruja native potato. The commercial var. Shepody showed pro-oxidant activity and had a relatively lower TPC. Results also indicated a higher concentration of total phenolics in the periderm of the colored native Chilean potatoes.